O003 The impact of wind farm noise in a laboratory setting on objective and subjective sleep efficiency. (7th October 2021) - Liebich, T; Lack, L; Micic, G; Hansen, K; Zajamsek, B; Dunbar, C; Lechat, B; Nguyen, D; Scott, H; Catcheside, P
Abstract: Introduction: Well-controlled studies of wind farm noise (WFN) on sleep are lacking despite complaints and known effects of other noise types on sleep. This laboratory-based study investigated the impact of continuous full-night WFN exposure replicated from field recordings on polysomnography-measured (objective) and sleep diary-determined (subjective) sleep efficiency compared to a quiet control night. Methods: Based on residential location and self-report data, 50 participants were categorised into three groups (14 living <10km from a wind farm and self-reporting sleep disturbance; 19 living <10km from a wind farm and self-reporting no sleep disturbance and 18 controls living in a quiet rural area). Participants underwent full in-laboratory polysomnography during exposure to continuous WFN (25 dB(A)) throughout the night and a quiet control night (background noise 19 dB(A)) in random order. Group and noise condition effects were examined via linear mixed model analysis. Results: Participants (30 females) were aged (mean±SD) 54.9±17.6 range: 18–80 years. Sleep efficiency in the control condition was (median [interquartile range]) objective: 85.5 [77.4 to 91.2]%; subjective: 85.7 [69.2 to 92.7]%) versus the WFN condition (objective: 86.1 [78.6 to 91.7]% subjective: 85.8 [66.2 to 93.8]%) with no significant main or interaction effects of group or noise condition (all p's >0.05). Conclusion: These results do not support that WFN at 25 dB(A) significantly impacts objective or subjective sleep efficiency in participants with or without prior WFN exposure or self-reported WFN-related sleep disturbance. Further analyses to investigate potential sleep micro-structural changes remain warranted.